Innate Immunity of Adipose Tissue in Rodent Models of Local and Systemic Staphylococcus aureus Infection - Andreas Schmid; Thomas Karrasch; Miriam Thomalla; Jutta Schlegel; Bernd Salzberger; Andreas Schäffler; Frank Hanses (Mediators of Inflammation)
Background. The role of adipose tissue in systemic inflammation during bacterial infection is unclear. Effects of Staphylococcus aureus infection on adipocytes in rodent models of experimental endocarditis and peritonitis, the impact of S. aureus infection on gene expression in epididymal and subcutaneous adipose tissue, and effects of S. aureus infection on the toll-like receptor-2- (TLR2-) cathelicidin pathway in vivo and in vitro were investigated. Material and methods. The rat model of catheter-induced S. aureus endocarditis and the mouse model of S. aureus-induced peritonitis were used for infection experiments, gene expression profiling in adipose tissue, and measurement of cytokines. 3T3-L1 adipocytes were analyzed for expression of the TLR2-cathelicidin pathway. Results. Upon systemic bacterial infection by S. aureus, there is a shift from anti- to proinflammatory cytokines in serum and in adipose tissue gene expression. The TLR2-cathelicidin pathway is increasingly expressed during adipocyte differentiation in vitro and is induced upon stimulation by synthetic lipopeptides. Conclusions. Systemic infection by Gram-positive bacteria induces proinflammatory transformation of adipose tissue sites distinct from infection sites, documented on the levels of gene expression and secreted mediators. The TLR2-cathelicidine pathway is expressed and highly inducible in adipocytes in vitro. Lipopeptides are important immune-modulators of adipocytes in both gene expression and protein secretion.